2015
DOI: 10.18052/www.scipress.com/ilns.39.10
|View full text |Cite
|
Sign up to set email alerts
|

Profitability of Coarse Cereals Production in India

Abstract: This study was aimed at investigating profitability of selected coarse cereals production in major producing states of India through analyzing cost, return and profitability of coarse cereals cultivation. Cost concepts and farm business income measures used for analysis the data ranging from 1980-81 to 2011-12. Net return of coarse cereals cultivation was observed to be highest for maize and it was highest in Bihar (Rs. 15,429/ha) and lowest Uttar Pradesh (Rs. -4,006/ha). Net return from cultivation of sorghum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 2 publications
1
3
0
Order By: Relevance
“…This result was in line with [9] Deshmukh who was reported that the BCR was 1.18 in small followed by 1.17 in medium and 1.16 in large farms. The results were in accordance with the results of [16], [17]. The coefficient of multiple determinations (Adjusted R2) was 0.81 which indicated that 82.9 per cent of the variation in dependent variables was explained by variation in independent variables.…”
Section: Profitability Of the Pearl Millet Growing Farmers In The Rainfed Ecosystemsupporting
confidence: 89%
“…This result was in line with [9] Deshmukh who was reported that the BCR was 1.18 in small followed by 1.17 in medium and 1.16 in large farms. The results were in accordance with the results of [16], [17]. The coefficient of multiple determinations (Adjusted R2) was 0.81 which indicated that 82.9 per cent of the variation in dependent variables was explained by variation in independent variables.…”
Section: Profitability Of the Pearl Millet Growing Farmers In The Rainfed Ecosystemsupporting
confidence: 89%
“…Except for maize, national policies towards major coarse cereals have not been effective like they are for wheat or rice, and hence they do not generate revenue [6] and do not encourage small farmers to cultivate these coarse cereals. For example, coarse grains such as bajra, jowar have not been included in the public distribution system (PDS) [2], and are not part of the Green Revolution to meet the food security of the nation [1] whereas maize is included in the PDS.…”
Section: Introductionmentioning
confidence: 99%
“…In TE 2011 to 2012, Karnataka had the highest share (14% of area and 18.32% of production). The share of maize area has declined steadily in Bihar* and Uttar Pradesh* between these two TE periods, which might be due to low benefit cost ratio of maize in both states than competing crops (Ayalew and Sekar, 2015). Share of Uttar Pradesh* has declined by more than half in area and production, whereas share of maize in Maharashtra has increased by about eight fold for area and about five fold for production.…”
Section: Trends and Share Of Maize Production In Indiamentioning
confidence: 96%